Afroeuropean Studies in Perspective - Krishnan, Madhu (Hungarian Journal of English and American Studies, 2021)
Book review: Beezmohun, Sharmilla, ed. Continental Shifts, Shifts in Perception: Black Cultures and Identities in Europe. Newcastle: Cambridge Scholars Publishing, 2016. 190 pages. ISBN 9781443888240. Hb. £41.99.